Analisa Sifat Mekanik Bahan Komposit Polimer Diperkuat Lembaran Serat Buah Pinang Akibat Beban Tarik - Ade Irwan; Fadly Ahmad Kurniawan Nasution; Muhammad Edy Pamuji (Fakultas Teknik UMSU, 2021)
The high availability of areca nut fibers makes it potential to be developed as an alternative material for polymer composites. This paper investigates the mechanical performance of unsaturated polyester resin composite materials reinforced with betel nut fibers. Areca fiber obtained from farmers is dried under the sun. The fibers made in finer fiber sheets which are glued together with an adhesive agent made from thermoplastic acrylic. Based on the results of the tensile test, this composite material has brittle material behaviours which is indicated by the low ability of the material to elongate. The maximum tensile strain of the areca fiber reinforced composite material is less than 2%. The stress-strain curve does not show a clear yield point and plastic zone, along with the fracture shape of the specimen that is perpendicular to the loading direction without any necking, which confirms that this composite material is not an elastic material. Based on the comparison of the number of fiber sheets, the specimen with two sheets of fiber showed a more optimal mechanical performance with a maximum tensile strength of 10.4023MPa and a Modulus of Elasticity of 709.0269MPa.